ANALISIS REKONSILIASI FISKAL PT DINAMIKA PRATAMA TAHUN 2020 - Kevin, Kevin; Widjaja, Purnamawati Helen (Jurnal Paradigma Akuntansi, 2024)
The purpose of this research is to determine the application of fiscal reconciliation to PT Dinamika Pratama commercial financial statements in 2020 and find out whether the PT Dinamika Pratama has calculated the Corporate Income Tax Payable under the law’s current tax. The method used in this research is qualitative descriptive analysis and the method of data collection is done through observation,documentation, and interviews with the company.The objects used are commercial financial statements 2020,corporate income tax ,and corporate annual tax return 2020.The results of the study indicate that the preparation of the fiscal financial statements at PT Dinamika Pratama is not in accordance with the UU PPh No 36 Tahun 2008,so it has an impact on the calculation of corporate income tax payable.